ANALYSIS OF WOMEN'S FIQIH TAHARAH STUDY IN ISLAMIC EDUCATION - Fauziah, Dina (Universitas Dharmawangsa, 2024)
Fiqh Thaharah has a broad discussion including thaharah haqiqiyah, namely thaharah rather than najis and thaharah hukmiyyah, namely thaharah rather than hadas. This research is a qualitative type through literature study with a content analysis process. Then, data or material from various primary and secondary sources is collected to provide accurate data regarding the research theme. In this discussion, there are three special bloods for women, namely menstrual blood, postpartum blood and istihadaha.